The relationship between Zikr (remembrance of Allah), heart coherence and intrapersonal communication among Muslim postgraduate students from different countries - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab (University Putra Malaysia (UPM), 2018)
A good level of heart coherence is important for individuals to overcome the emotional and psychological stresses and conduct proper communication with one another. Zikr or remembrance of Allah, as the main pleasing performance to Allah, has direct effects on the emotional and psychological situation of Muslims. The levels of heart coherence and the effects of any intervention on the rhythmic actions and reactions of human heart are measurable through the use of heart rate variability (HRV)-biofeedback technology and HRV techniques. Thus, this study was conducted through the application of a mixed method research design, which included the use of HRV-biofeedback technology and some interviews, to assess the probable relationship between Ziki, heart coherence and intrapersonal communication of Muslim university students from different nationalities. This study had 20 participants from 10 different countries. From all participants, six of them were interviewed to support the HRV data through their direct views. The results from this study confirmed the existence of a close relationship between Zikr and the levels of heart coherence among the participants. Based on the results, Zikr performance had significant positive effects on the increase of heart coherence among the participants, and heart coherence is among the main factors that affect the process of intrapersonal communication within the human body. The results from this study may encourage individuals to perform Zikr performance as an effective treatment for their emotional and psychological disorders.